Konstytucja — system — hegemonia. „Antypolityczna” funkcja argumentów systemowych w orzecznictwie konstytucyjnym - Sulikowski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The main purpose of this paper is to examine the function of arguments based on so called systemic interpretation of law in constitutional jurisprudence, using methods and tools offered by the post-analytical, critical philosophy in the field of legal theory. The author notes that constitutional courts apply the systemic argumentation to hide real, political motives of their decisions. The author tries to diagnose the potential impact of this phenomenon on the functioning of liberal democracy, refering to theories developed by C. Lefort, Ch. Mouffe, E. Laclau and J. Habermas. In the Author’s opinion the constitutional activism, which has been masked by the systemic interpretation, is based on the liberal utopia of creation of law without ‟the political”. The rise of populist political forces in Europe can be considered as reaction to the constitutional activism and the crisis of the ‟liberal dream”.
Keywords: orzecznictwo konstytucyjne; konstytucja; hegemonia; system prawa; argumenty systemowe